Detecting sills as kinematic indicators based on spectral decomposition - Inferring stress regime in the Malay Basin (Fractured basement reservoir) - Shamsuddin, A.A.S. (European Association of Geoscientists and Engineers, EAGE, 2019)
Seismic imaging issues and approaches which are related to resolution hinder the understanding of the fractured basement in terms of geological complexities of rock types and tectonic regime. They were implemented in detecting mesoscopic scale fracture. In principle, fracture scale varies and its combination is defined as fracture network. A study was conducted by integrating surface and subsurface in order to enhance the understanding of the fractured basement. In this study, we provide the kinematic indicators as structural evidences in inferring and enhancing the understanding of stress regime. Outcrop analysis provides new insight on the complexity of the fractured basement where kinematic indicators, dolerite dykes were observed in the Peninsular Malaysia (Eastern part). In the fractured basement of the Malay Basin, spectral decomposition was used to detect kinematic indicators, sills. The results presented in this paper are consistent with existing igneous rocks that were observed in the core and cutting. This study proposes horizontal shortening during sills emplacement in the N-S to NW-SE orientations, followed by sinistral motion in subsurface area and dyke in surface area suggests horizontal extension. Dyke-sill influence in the fracture basement area needs further study in order to evaluate source/reservoir potential of the fractured basement reservoir. Â© 2019 Asia Petroleum Geoscience Conference and Exhibition, APGCE 2019. All rights reserved.